Remote Sensing Technologies and Applications in Urban Environments II 2017
DOI: 10.1117/12.2278422
|View full text |Cite
|
Sign up to set email alerts
|

A local segmentation parameter optimization approach for mapping heterogeneous urban environments using VHR imagery

Abstract: Mapping large heterogeneous urban areas using object-based image analysis (OBIA) remains challenging, especially with respect to the segmentation process. This could be explained both by the complex arrangement of heterogeneous land-cover classes and by the high diversity of urban patterns which can be encountered throughout the scene. In this context, using a single segmentation parameter to obtain satisfying segmentation results for the whole scene can be impossible. Nonetheless, it is possible to subdivide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…An important advantage of the proposed method is its potential for automation with particular merit for large, heterogeneous areas. As Grippa et al [47] and Georganos et al [48] pointed out, in heterogeneous urban scenes a single set of segmentation parameters is inadequate and less efficient than spatially partitioning the study area into several subsets and optimizing each separately. Similar studies for semi-rural and agricultural environments have demonstrated the efficacy of local optimization through the use of F-measure and ESP methods [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…An important advantage of the proposed method is its potential for automation with particular merit for large, heterogeneous areas. As Grippa et al [47] and Georganos et al [48] pointed out, in heterogeneous urban scenes a single set of segmentation parameters is inadequate and less efficient than spatially partitioning the study area into several subsets and optimizing each separately. Similar studies for semi-rural and agricultural environments have demonstrated the efficacy of local optimization through the use of F-measure and ESP methods [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…The second data set consists of a very-high resolution land-cover map, derived from the Pleiades pan-sharpened tri-stereo images of 2015, with a spatial resolution of 0.5 m (see Figure 3). This map was previously produced thanks to a semi-automated open-source framework for object-based image analysis and supervised classification [21][22][23]. The overall accuracy (OA) of this product achieved 89.5%, and the building class reached 94% and 97% for user and producer accuracy, respectively (more details about the validation of this product are provided in [24]).…”
Section: Remote Sensing Derived Datamentioning
confidence: 99%
“…To meet our needs, we developed a new GRASS GIS add-on, called i.segment.uspo, based on the best-performing state-of-the-art methods [7] for unsupervised segmentation parameter optimization (USPO). Recently, we proved that optimizing the segmentation parameter on a local basis in large and heterogenous urban scene allowed to improve the land cover classification outputs [8], [9].…”
Section: Big Data and Automation For Object-based Land Cover Mappingmentioning
confidence: 99%